1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Particle projectile angle help

  1. Dec 9, 2007 #1
    1. The problem statement, all variables and given/known data

    A particle is projected at an angle alpha above the horizontal from a point on the edge of a table of height h standing on a horizontal floor. The particle reaches the floor at a point whose horizontal distance from the point of projection is 2h. Show that when it strikes the floor, the inclination theta below the horizontal of its direction of motion is given by

    tan(theta) = tan(alpha) + 1

    3. The attempt at a solution

    okay i can manage to prove upto :

    tan(theta) = tan(alpha) - gt/vi cos(alpha)

    but i don't know what to do next... or rather what i do next doesn't make the fraction part equal 1

    help would be much appreciated

    Attached Files:

    • q7.jpg
      File size:
      7.7 KB
    Last edited: Dec 9, 2007
  2. jcsd
  3. Dec 9, 2007 #2
    this might help...

    is the method correct?

    Attached Files:

  4. Dec 10, 2007 #3

    Shooting Star

    User Avatar
    Homework Helper

    (I was not quite able to read all your calculations, so I’ll give you a derivation my way.)

    I’m writing ‘a’ for alpha and ‘b’ for theta, for convenience. The total time is t. Also, I’m writing u for the initial velo and v for the final velo.

    u(cos a)t = 2h => t = 2h(ucos a) ..(1).
    [Also, u cos a = v cos b, since they’re horz components.]

    v^2 = u^2 + 2gh => h = (v^2 –u^2)/2g ..(2)

    The eqn for y is: y = u(sin a)t – (1/2)gt^2. Putting (-h) in place of y,

    -h = u(sin a)t – (1/2)gt^2
    -h = (u*sin a)2h/ucos a –(1/2)g *4h^2/(u^2 cos^2 a) (from 1 putting value of t)
    -1 = 2tan a – 2gh/(ucos a)^2
    -1 = 2tan a – [2g/(ucos a)^2]( v^2 –u^2)/2g (from 2 putting value of h)
    -1 = 2tan a – (v^2 –u^2)/(ucos a)^2
    -1 = 2tan a – v^2/(ucos a)^2 – u^2)/(ucos a)^2
    -1 = 2tan a – v^2/(vcos b)^2 + u^2)/(ucos a)^2 (since ucos a = vcos b)
    -1 = 2tan a – sec^2 b + sec^2 a [put sec^2 = 1 + tan^2]
    tan^2 b = (tan a + 1)^2, after some simplification. So,

    tan(theta) = tan(alpha) + 1, taking the +ve value.
    Last edited: Dec 10, 2007
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook